Breaking the Ceiling of Human Maximal Life span. (7th November 2017) - Ben-Haim, Moshe Shay; Kanfi, Yariv; Mitchell, Sarah J; Maoz, Noam; Vaughan, Kelli L; Amariglio, Ninette; Lerrer, Batia; de Cabo, Rafael; Rechavi, Gideon; Cohen, Haim Y
Abstract: While average human life expectancy has increased dramatically in the last century, the maximum life span has only modestly increased. These observations prompted the notion that human life span might have reached its maximal natural limit of ~115 years. To evaluate this hypothesis, we conducted a systematic analysis of all-cause human mortality throughout the 20th century. Our analyses revealed that, once cause of death is accounted for, there is a proportional increase in both median age of death and maximum life span. To examine whether pathway targeted aging interventions affected both median and maximum life span, we analyzed hundreds of interventions performed in multiple organisms (yeast, worms, flies, and rodents). Three criteria: median, maximum, and last survivor life spans were all significantly extended, and to a similar extent. Altogether, these findings suggest that targeting the biological/genetic causes of aging can allow breaking the currently observed ceiling of human maximal life span.